What patients with diabetes mellitus type 2 know on their disease - Belkis Mercedes Vicente Sánchez; Gisela Zerquera Trujillo; Elodia M. Rivas Alpizar; José A. Muñoz Cocina; Yaremy Teresita Gutiérrez Cantero; Eduardo Castañedo Álvarez (Medisur)
Background: education on diabetes is one of the key objectives of general care for people with diabetes mellitus and should be effectively implemented in order to provide patients with more information about their disease. Objective: to determine how much patients with type 2 diabetes know about the disease. Methods: descriptive study of a case series conducted between January and June 2008. The universe consisted on 120 patients from the "Area V" Polyclinic of Cienfuegos who were diagnosed with diabetes mellitus, type 2. In order to determine how much patients know about the disease a pre-test designed by the working group of the Center for Diabetes Care and Education was applied to all patients admitted in the institution. Results: females predominated over males. The largest number of patients was between 5 and 10 years and more than 10 years of disease progression (40% in both groups). In the first group 21, 7% of patients have an inadequate knowledge standard on the disease and in the second one, the same situation occurs in 25% of them. Hypertension and ischemic heart disease were the chronic diseases associated with more patients and polyneuropathy and neuropathy were the most common chronic complications. Conclusions: patients with diabetes need a steady educational work to acquire more knowledge on their disease and to live better with it.